The Eruption of Mount Raung and Traces of Classical Cultural Heritage in The 15th - 16th Centuries in Bondowoso Regency - Pratama, Akhmad Ryan; Jamil, Robit Nurul; Swastika, Kayan; Puja, Gusti Ngurah Ary Kesuma; Na’im, Mohamad (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
Research into the classical period in Bondowoso Regency has yet to provide a clear description of its archaeological remains. Between 2009 and 2020, numerous artifacts from the classical period were discovered, including kepeng money, ancient brick structures, and Majapahit-style wells buried 1 to 5 meters deep. No inscriptions definitively link these relics to the Majapahit kingdom, but their presence indicates that Bondowoso is rich in classical cultural artifacts. This study aims to investigate the historical traces of classical civilization in Bondowoso Regency, influenced by Hindu-Buddhist culture, which have not been thoroughly examined. The main objective of this research is to document and analyze the classical cultural remains in Bondowoso Regency, focusing on the number, type, form, and function of these artifacts. Accurate data on the distribution, quantity, and characteristics of these remains are essential for academic research, cultural heritage preservation, and tourism development. The research employs a historical method supported by archaeological approaches. This combined methodology is chosen for its effectiveness in addressing the research objectives, which rely heavily on the analysis of archaeological evidence, such as artifacts, structures, and buildings. The archaeological approach enhances the historical method by providing tangible data and context. Initial conclusions suggest that the classical civilization in Bondowoso began to decline due to the eruption of Mount Raung in the 16th century. This research contributes to a deeper understanding of Bondowoso's historical and cultural landscape, highlighting the significance of its classical period remains. In summary, this study provides a comprehensive examination of the classical cultural artifacts in Bondowoso Regency, aiming to clarify their historical context and significance. The findings are expected to offer valuable insights for further academic research and contribute to the preservation and promotion of Bondowoso's cultural heritage.